Electromyographic activity of quadriceps muscle during functional activities in participants with and without patellofemoral pain - Herbst, Johannes Albertus (My University, 2017)
Background: Patellofemoral pain (PFP) is a common knee complaint associated with pain around the patella. Research has identified altered electromyographic (EMG) activity of the knee muscles in individuals with PFP compared to a healthy population (Briani et al., 2016). Purpose: The purpose of this observational study was to identify the EMG activity of the quadriceps muscle during functional activities in participants experiencing PFP and participants with no PFP. Methods: The onset and sequence timing including the ranking and Q-angle in relation to the rectus femoris (RF), vastus medialis obliquus (VMO) and vastus lateralis (VL) activity was measured with surface EMG in 17 PFP participants and 17 controls during a sit to stand, squat, and step up and step down. Results: The RM-ANOVA discovered a significant difference in the onset of VMO compared to RF muscle between the activities in the PFP group (-0.11 to 0.07 sec; p = 0.03) and the healthy group (-0.18 to -0.03; p = <0.01), as well as the VL compared to the RF muscle in the PFP group (-0.07 to 0.13 sec; p = <0.01). Significant differences were shown comparing the ranking of EMG onset for the quadriceps muscle to each activity in the healthy group (p = <0.01 to 0.04), and in the PFP group for the sit to stand (p = 0.01). Onset of VMO activity was predominantly ranked first in the healthy group (56%) and the VL in the PFP group (44%). A Mann-Whitney U-test shown a significant relationship in the healthy group between the Q-angle and the VMO, VL and RF muscles during the step down activity (r = -0.53 to -0.55; p = 0.02 to 0.03). Conclusion: This study confirms that the quadriceps muscle responds differently to different functional activities in the PFP and healthy population respectively. The healthy group tend to utilize the VMO first, compared to the PFP group with altered onset of quadriceps activation. Furthermore, the greater the Q-angle is, the earlier the onset of quadriceps muscle will be in the healthy group. This relationship was not found in the PFP group.
A research report submitted to the Faculty of Health Sciences, University of the Witwatersrand, in partial fulfillment of the requirements for the degree of Master of Science in Medicine in the field of Biokinetics Johannesburg, 2017
Keywords: Quadriceps Muscle Patellofemoral Pain